Relación de la inteligencia emocional con el rendimiento académico en jóvenes en el distrito turístico y cultural de Riohacha (2020)
Being clear about the fundamental role that emotions play in our lives, we are deeply motivated by being able to approach the relationship between emotional intelligence and academic performance through our research. In this study, the objective of establishing the relationship between emotional intelligence and academic performance in high school youth in the tourist and cultural district of Riohacha is proposed. The sample is made up of 37 high school students from 13 to 17 years of age, for the evaluation of the variables the TMMS-24 scale and the record of the final grades of the previous year have been used. The results obtained show us a significant relationship between emotional regulation and academic performance, it was not found with the dimensions of attention and emotional clarity. Most of the study subjects have high and basic performance. Regarding the levels of emotional intelligence, we find in emotional attention most of the subjects have adequate emotional attention corresponding to 78.38%, in emotional clarity 54.05% of the population should improve it and 45.95% have adequate emotional understanding, regarding emotional repair 51.35% have adequate emotional repair, followed by 43.24% who have excellent regulation of their emotions. The results show us the importance of deepening the relationship between emotional intelligence and academic performance.